Effects of Planting Methods on Growth, Yield and Fruit Quality of Selected Banana (Musa AAA) Clones (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted at the experimental farm of theNational Institute for the Promotion of Horticultural Exports, Universityof Gezira, Sudan, during 2007/08. The objective was to study the effectsof planting methods on growth, yield and fruit quality of three bananaclones. Methods of planting were planting banana suckers in flats,furrows or in beds. In-row and inter-row spacing of planting was 3m and2m, respectively. Three banana clones were used, namely, WilliamsHybrid (WH), Grand Nain (GN) (introduced clones) and the local cloneDwarf Cavendish (DC). Split-plot design with three replicates was used,where planting methods were the main plots and banana clones were thesub-plots. Results showed that planting methods had significant effects onvegetative growth, yield and fruit quality of bananas, regardless of theclone used. Furrow planting resulted in the tallest plants with the thickestpseudostems and the highest yield followed by the flat method and thenbed method. The introduced clones WH and GN were taller, with thickerpseudostems and higher yields than the local clone DC. The clone WH,planted in furrows, took the longest duration from planting to shooting;however, it took the shortest period from shooting to harvesting. Thehighest total soluble solids of fruits were obtained by the bed plantingmethod.
Keywords: Planting system; banana clones; vegetative growth; yield fruit quality